Employee motivation and productivity: A case study of Zambia’s selected middle tier banks - Louis Mwaba; Javaid Dar (International Journal of Academe and Industry Research)
Employee motivation and employee productivity remain among the critical areas that are key to the growth of developing countries and organisations. This paper explores employee motivation and productivity in the middle-tier banks in Zambia through connecting the relationship between motivation and productivity and highlights the factors that drive motivation and productivity. The research study was conducted through qualitative research and semi-structured interviews, direct observation and qualitative questionnaires were used as data collection instruments. The emerging theme from the study was competitive remuneration but this has a limited impact. In addition, quality of leadership emerged as the other theme with three sub-themes, which were management style, participative leadership, and balancing work life dynamics. The other themes that emerged were performance management, growth and development and organisational culture. The study has policy implications not only for leaders in the banking sector but also for policymakers in government, as some of the emerging themes could extend into other sectors. The study concludes that there is a strong relationship between employee motivation whether intrinsic or extrinsic and employee productivity in organisations.